Process for preparing coal gangue brick by utilizing ash of tobacco and garbage
By combining coal gangue with tobacco carbon composite adsorption powder and other materials, coal gangue bricks are prepared, which solves the problems of spontaneous combustion and environmental pollution of coal gangue mountains, and achieves efficient utilization of resources and improves the environmental protection of bricks.
Patent Information
- Application Number
- CN202411891589.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Due to its low calorific value and combustibility, coal gangue mountains are prone to weathering and spontaneous combustion, releasing toxic and harmful gases, polluting the atmosphere and causing harm to human health. At the same time, the accumulation of coal gangue wastes land resources, resulting in a serious threat to the environment and human health.
A process is adopted to mix materials such as coal gangue coarse aggregate, fine aggregate, garbage incineration fly ash, river sand, fly ash, cement and tobacco carbon composite adsorption powder after stirring and mixing, adding binder and water, stirring for 100-120r/min for 1-1.5min, then add dry mixture and continue to stir for 1.5-2min to form a dry mixture, and then vibrating, holding pressure in the mold, and then curing under specific conditions after being demolded to prepare coal gangue bricks.
Through this process, the tobacco and garbage ash resources are fully utilized, the leaching of heavy metals in coal gangue bricks is reduced, the environmental protection and use value of bricks are improved, and the mechanical strength and stability of coal gangue bricks are enhanced.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coal gangue bricks, and in particular relates to a process for preparing coal gangue bricks by utilizing tobacco and garbage ash. Background Art
[0002] Gangue heaps are places where coal mines and coal preparation plants concentrate solid waste. They are mainly composed of gangue discharged during coal mining and coal washing. Gangue is mainly composed of minerals such as quartz, clay minerals, and carbonates. Its chemical composition is mainly silicon, aluminum, and iron oxides, and also contains a small amount of heavy metals and other elements. Due to its low calorific value and flammability, gangue piled in the open air is prone to weathering and spontaneous combustion, releasing toxic and harmful gases such as sulfur dioxide and nitrogen oxides, which pollute the atmosphere and cause harm to human health.
[0003] The piles of coal gangue not only waste land resources, but also cause spontaneous combustion, rain, mudification, etc., posing a serious threat to the environment and human health. In order to reduce the occupation of land resources and environmental impact of coal gangue and promote the development of circular economy, high value-added utilization methods such as underground filling, production of building materials, and recovery of mineral products have been extended. For example, coal gangue can be used to produce ordinary Portland cement, special cement and clinker-free cement, and can also be burned to make lightweight aggregates for concrete production, and even precious rare metals can be extracted from it. The patent application with publication number CN102399111A discloses an ecological restoration matrix and plant restoration technology for coal gangue mountains in coal mining areas, and explores the growth and greening technology of tobacco and nightshade in the coal gangue greening matrix, providing a new way out for the reclamation and greening of coal gangue mountains.
[0004] The method of using tobacco to repair coal gangue mountains is not a long-term solution, and it will increase the economic and environmental burden of subsequent treatment of tobacco straw. Therefore, the coal gangue needs to be utilized as a resource in the end. However, coal gangue contains heavy metal elements, which are easily leached when prepared into coal gangue bricks, and there is still a risk of pollution. Summary of the invention
[0005] The purpose of the present invention is to provide a process for preparing gangue bricks by using tobacco and garbage ash, so as to make full use of tobacco resources in the process of repairing gangue mountain and reduce the leaching of heavy metals in gangue bricks.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A process for preparing coal gangue bricks using tobacco and garbage ash comprises the following steps:
[0008] Coal gangue coarse aggregate, coal gangue fine aggregate and waste incineration fly ash are stirred and mixed to obtain a dry mixture; river sand, fly ash, cement and tobacco carbon composite adsorption powder are stirred and mixed, and then a binder, a water reducer and water are added, and stirred at 100-120r / min for 1-1.5min, and then the dry mixture is added and stirred for 1.5-2min, and after mixing evenly, it is transferred to a mold, vibrated for 20-30s, and maintained at a pressure of 1.6-1.8MPa for 25-30s. After demolding, it is cured for 12-15 days at 20-25℃ and a humidity of 90-95% to prepare coal gangue bricks, thereby completing the process of preparing coal gangue bricks using tobacco and garbage ash.
[0009] Furthermore, the particle size of the gangue coarse aggregate is 5-10 mm, the particle size of the gangue fine aggregate is 2-4 mm, and the particle size of the river sand is 0.2-0.5 mm.
[0010] Furthermore, the mass ratio of gangue coarse aggregate, gangue fine aggregate, waste incineration fly ash, river sand, fly ash, cement, tobacco carbon composite adsorption powder, binder, water reducer and water is 60-70:30-40:10-15:20-30:5-10:15-25:5-8:2-3:0.4-0.5:7.5-10.5.
[0011] Furthermore, the binder is mixed with polyvinyl alcohol and silica sol in a mass ratio of 1:1-1.5.
[0012] Furthermore, the water reducer is a naphthalene-based water reducer or a polycarboxylic acid high-efficiency water reducer.
[0013] Furthermore, the tobacco-carbon composite adsorption powder is prepared by the following steps:
[0014] Step 1: Cut the dry tobacco into small pieces with a diameter of 3±0.5 cm, then crush them with a pulverizer, pass through a 50-60 mesh sieve to obtain tobacco powder, mix the tobacco powder and coal gangue catalytic particles in a mass ratio of 5-6:1 and transfer them to a carbonization furnace. Under nitrogen protection, heat the mixture to 300-320°C at a rate of 3-5°C / min, keep the temperature for 100-120 minutes, cool naturally, pass through a 60 mesh sieve, remove the coal gangue catalytic particles, and obtain tobacco carbon powder.
[0015] Step 2: Add tobacco powder, calcium chloride and deionized water into a reactor and stir to mix, then add diammonium hydrogen phosphate into the reactor, adjust the pH value to 10-10.5 with ammonia water, stir at a speed of 200-300 r / min for 2-2.5 hours, let stand for aging for 20-24 hours, filter, wash the filter cake with deionized water for 2-3 times, and vacuum dry to obtain hydroxyapatite composite tobacco powder.
[0016] Step 3: Add hydroxyapatite composite tobacco carbon powder, anhydrous ethanol, deionized water and silane coupling agent KH-550 into a reactor, adjust the pH value to 3 with acetic acid, stir at 200-300 r / min for 15-30 min, then ultrasonically disperse for 15-30 min, stir and react at 65-70° C. for 3-4 h, filter, wash the filter cake with anhydrous ethanol 2-3 times, and vacuum dry to obtain silane coupling agent modified composite tobacco carbon powder.
[0017] Step 4: Add the silane coupling agent modified composite tobacco carbon powder and the mixed solvent into the reactor, stir and mix, then add triethylenetetramine into the reactor, stir and aminize for 2.5-3h at 70-80°C and 200-300r / min, cool to 25°C, add carbon disulfide and sodium hydroxide into the reactor, stir and react for 2-2.5h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry to obtain tobacco carbon composite adsorption powder.
[0018] Furthermore, the usage ratio of tobacco carbon powder, calcium chloride, deionized water and diammonium hydrogen phosphate is 2-2.5 g: 11 g: 180-200 mL: 7.9 g.
[0019] Furthermore, the dosage ratio of hydroxyapatite composite tobacco carbon powder, anhydrous ethanol, deionized water and silane coupling agent KH-550 is 10g:100mL:50mL:3g.
[0020] Furthermore, the usage ratio of the silane coupling agent modified composite tobacco carbon powder, the mixed solvent, triethylenetetramine, carbon disulfide and sodium hydroxide is 1g:40-50mL:1-1.5g:0.66-0.995g:6g.
[0021] Furthermore, the mixed solvent is prepared by mixing ethylene glycol and deionized water in a volume ratio of 1:1.
[0022] Furthermore, the gangue catalytic particles are prepared by the following steps:
[0023] The coal gangue is crushed, sieved and transferred to a tubular furnace. Under nitrogen protection, the temperature is raised to 800-820°C at a rate of 5-10°C / min, kept warm for 50-60 minutes, and cooled naturally to obtain coal gangue catalytic particles with a particle size of 1-1.2 mm.
[0024] Beneficial effects of the present invention:
[0025] The process for preparing gangue bricks by using tobacco and garbage ash of the present invention fully utilizes various waste resources such as tobacco for ecological restoration and garbage crushing fly ash, which is green and environmentally friendly.
[0026] The raw material of the coal gangue catalytic particles used in the carbonization of tobacco in the present invention is also coal gangue. After high-temperature pyrolysis, the surface of the coal gangue becomes rougher and the porosity increases, which is helpful to adsorb tobacco tar and catalyze the cracking of tar, thereby reducing the pollution of tobacco tar to carbonization equipment. As a kind of biochar, tobacco carbon powder has good adsorption effect. After reacting with calcium chloride and diammonium hydrogen phosphate, the formed hydroxyapatite is deposited in the tobacco carbon powder, which helps to enhance the mechanical strength of the tobacco carbon powder and improve the stability of the tobacco carbon powder. Through its ion exchange and complexation, it helps to increase the fixation effect of the tobacco carbon composite adsorption powder on heavy metals. Triethylenetetramine is grafted onto the modified composite tobacco carbon powder through the silane coupling agent KH-550, and then reacted with carbon disulfide and sodium hydroxide in a mixed solvent. The formed product contains dithiocarbamic acid functional groups, which have a good capture effect on heavy metals, further increasing the fixation effect of the tobacco carbon composite adsorption powder on heavy metals, thereby reducing the leaching of heavy metals in coal gangue bricks, which is conducive to the environmentally friendly application of coal gangue bricks.
[0027] The raw materials of the coal gangue bricks of the present invention also include waste incineration fly ash. The calcium oxide content in the waste incineration fly ash is relatively high. By optimizing the raw material ratio, it can complement the coal gangue with a low calcium oxide content, which is helpful for the resource utilization of waste fly ash. At the same time, it can also generate hydrated calcium silicate and hydrated calcium aluminate with silicon oxide and aluminum oxide in the raw materials to form a high-strength network structure, thereby increasing the splitting tensile strength of the coal gangue bricks. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1: A process for preparing coal gangue bricks using tobacco and garbage ash, comprising the following steps:
[0030] S1: The coal gangue was crushed, sieved and transferred to a tubular furnace. Under nitrogen protection, the temperature was raised to 800°C at a rate of 5°C / min, kept at this temperature for 50 minutes, and cooled naturally to obtain coal gangue catalytic particles with a particle size of 1 mm.
[0031] S2: Cut the dry tobacco into small pieces with a diameter of 3±0.5 cm, then crush them with a pulverizer, pass them through a 50-mesh sieve to obtain tobacco powder, mix the tobacco powder and coal gangue catalytic particles in a mass ratio of 5:1 and transfer them to a carbonization furnace. Under nitrogen protection, heat the mixture to 300°C at a rate of 3°C / min, keep the temperature for 100 minutes, cool it naturally, pass it through a 60-mesh sieve, remove the coal gangue catalytic particles, and obtain tobacco carbon powder.
[0032] S3: Add 20 kg tobacco powder, 110 kg calcium chloride and 1800 L deionized water into a reactor and stir to mix, then add 79 kg diammonium phosphate into the reactor, adjust the pH value to 10 with ammonia water, stir at a speed of 200 r / min for 2 hours, let stand for aging for 20 hours, filter, wash the filter cake twice with deionized water, and vacuum dry to obtain hydroxyapatite composite tobacco powder.
[0033] S4: 10 kg hydroxyapatite composite tobacco carbon powder, 100 L anhydrous ethanol, 50 L deionized water and 3 kg silane coupling agent KH-550 were added into a reactor, the pH value was adjusted to 3 with acetic acid, stirred at 200 r / min for 15 min, ultrasonically dispersed for 15 min, stirred at 65 ° C for 3 h, filtered, washed the filter cake twice with anhydrous ethanol, and vacuum dried to obtain silane coupling agent modified composite tobacco carbon powder.
[0034] S5: Add 10kg of silane coupling agent modified composite tobacco carbon powder and 400L of mixed solvent into a reactor and stir to mix, then add 10kg of triethylenetetramine into the reactor, stir and aminize for 2.5h at 70℃ and 200r / min, cool to 25℃, add 6.6kg of carbon disulfide and 60kg of sodium hydroxide into the reactor, stir and react for 2h, filter, wash the filter cake with deionized water and anhydrous ethanol twice respectively, and vacuum dry to obtain tobacco carbon composite adsorption powder, wherein the mixed solvent is a mixture of ethylene glycol and deionized water in a volume ratio of 1:1.
[0035] S6: 60kg of coarse coal gangue aggregate with a particle size of 5-10mm, 30kg of fine coal gangue aggregate with a particle size of 2-4mm and 10kg of fly ash from garbage incineration are stirred and mixed to obtain a dry mixture; 20kg of river sand with a particle size of 0.2-0.5mm, 5kg of fly ash, 15kg of cement and 5kg of tobacco carbon composite adsorption powder are stirred and mixed, 2kg of binder, 0.4kg of naphthalene-based water reducer and 7.5kg of water are added, wherein the binder is a mixture of polyvinyl alcohol and silica sol in a mass ratio of 1:1, stirred at 100r / min for 1min, and then the dry mixture is added and stirred for 1.5min. After mixing evenly, the mixture is transferred to a mold, vibrated for 20s, maintained at a pressure of 1.6MPa for 25s, and cured for 12 days at 20°C and a humidity of 90% after demolding to prepare coal gangue bricks, completing the process of preparing coal gangue bricks using tobacco and garbage ash.
[0036] Example 2: A process for preparing gangue bricks using tobacco and garbage ash, comprising the following steps:
[0037] S1: The coal gangue was crushed, sieved and transferred to a tubular furnace. Under nitrogen protection, the temperature was raised to 810°C at a rate of 8°C / min, kept at this temperature for 55 minutes, and cooled naturally to obtain coal gangue catalytic particles with a particle size of 1.1 mm.
[0038] S2: Cut the dry tobacco into small pieces with a diameter of 3±0.5 cm, then crush them with a pulverizer and pass them through a 50-mesh sieve to obtain tobacco powder. Mix the tobacco powder and coal gangue catalytic particles in a mass ratio of 5.5:1 and transfer them to a carbonization furnace. Under nitrogen protection, heat the mixture to 310°C at a rate of 4°C / min, keep the temperature for 110 min, cool it naturally, pass it through a 60-mesh sieve, remove the coal gangue catalytic particles, and obtain tobacco carbon powder.
[0039] S3: Add 22.5 kg tobacco powder, 110 kg calcium chloride and 1900 L deionized water into a reactor and stir to mix, then add 79 kg diammonium phosphate into the reactor, adjust the pH value to 10.2 with ammonia water, stir at a speed of 250 r / min for 2.2 h, let stand for aging for 22 h, filter, wash the filter cake twice with deionized water, and vacuum dry to obtain hydroxyapatite composite tobacco powder.
[0040] S4: 10 kg hydroxyapatite composite tobacco carbon powder, 100 L anhydrous ethanol, 50 L deionized water and 3 kg silane coupling agent KH-550 were added into a reactor, the pH value was adjusted to 3 with acetic acid, and the mixture was stirred at 250 r / min for 20 min and then ultrasonically dispersed for 20 min. The mixture was stirred at 68 °C for 3.5 h, filtered, and the filter cake was washed twice with anhydrous ethanol and vacuum dried to obtain silane coupling agent modified composite tobacco carbon powder.
[0041] S5: Add 10kg of silane coupling agent modified composite tobacco carbon powder and 450L of mixed solvent into a reactor and stir to mix, then add 12.5kg of triethylenetetramine into the reactor, stir and aminize for 2.8h at 75℃ and 250r / min, cool to 25℃, add 8kg of carbon disulfide and 60kg of sodium hydroxide into the reactor, stir and react for 2.2h, filter, wash the filter cake with deionized water and anhydrous ethanol twice respectively, and vacuum dry to obtain tobacco carbon composite adsorption powder, wherein the mixed solvent is a mixture of ethylene glycol and deionized water in a volume ratio of 1:1.
[0042] S6: 65 kg of gangue coarse aggregate with a particle size of 5-10 mm, 35 kg of gangue fine aggregate with a particle size of 2-4 mm and 12.5 kg of waste incineration fly ash are stirred and mixed to obtain a dry mixture; 25 kg of river sand with a particle size of 0.2-0.5 mm, 8 kg of fly ash, 20 kg of cement, and 6.5 kg of tobacco carbon composite adsorption powder are stirred and mixed, and 2.5 kg of binder, 0.45 kg of naphthalene water reducer and 9 kg of water are added, wherein The binder is mixed with polyvinyl alcohol and silica sol in a mass ratio of 1:1.2, stirred at 110r / min for 1.2min, and then the dry mixture is added and stirred for 1.8min. After mixing evenly, it is transferred to a mold, vibrated for 25s, and maintained at a pressure of 1.7MPa for 28s. After demolding, it is cured at 22°C and a humidity of 92% for 13 days to prepare coal gangue bricks, completing the process of preparing coal gangue bricks using tobacco and garbage ash.
[0043] Example 3: A process for preparing gangue bricks using tobacco and garbage ash, comprising the following steps:
[0044] S1: The coal gangue was crushed, sieved and transferred to a tubular furnace. Under nitrogen protection, the temperature was raised to 820°C at a rate of 10°C / min, kept warm for 60 minutes, and naturally cooled to obtain coal gangue catalytic particles with a particle size of 1.2 mm.
[0045] S2: Cut the dry tobacco into small pieces with a diameter of 3±0.5 cm, then crush them with a pulverizer and pass them through a 60-mesh sieve to obtain tobacco powder. Mix the tobacco powder and coal gangue catalytic particles in a mass ratio of 6:1 and transfer them to a carbonization furnace. Under nitrogen protection, heat the mixture to 320°C at a rate of 5°C / min, keep the temperature for 120 min, cool it naturally, pass it through a 60-mesh sieve, remove the coal gangue catalytic particles, and obtain tobacco carbon powder.
[0046] S3: Add 25 kg tobacco powder, 110 kg calcium chloride and 2000 L deionized water into a reactor and stir to mix, then add 79 kg diammonium phosphate into the reactor, adjust the pH value to 10.5 with ammonia water, stir at a speed of 300 r / min for 2.5 h, let stand for 24 h, filter, wash the filter cake with deionized water for 3 times, and vacuum dry to obtain hydroxyapatite composite tobacco powder.
[0047] S4: 10 kg hydroxyapatite composite tobacco carbon powder, 100 L anhydrous ethanol, 50 L deionized water and 3 kg silane coupling agent KH-550 were added into a reactor, the pH value was adjusted to 3 with acetic acid, stirred at 300 r / min for 30 min, ultrasonically dispersed for 30 min, stirred at 70 ° C for 4 h, filtered, washed the filter cake with anhydrous ethanol for 3 times, and vacuum dried to obtain silane coupling agent modified composite tobacco carbon powder.
[0048] S5: Add 10kg of silane coupling agent modified composite tobacco carbon powder and 500L of mixed solvent into a reactor and stir to mix, then add 15kg of triethylenetetramine into the reactor, stir and aminize for 3h at 80℃ and 300r / min, cool to 25℃, add 9.95kg of carbon disulfide and 60kg of sodium hydroxide into the reactor, stir and react for 2.5h, filter, wash the filter cake with deionized water and anhydrous ethanol for 3 times respectively, and vacuum dry to obtain tobacco carbon composite adsorption powder, wherein the mixed solvent is a mixture of ethylene glycol and deionized water in a volume ratio of 1:1.
[0049] S6: 70kg of gangue coarse aggregate with a particle size of 5-10mm, 40kg of gangue fine aggregate with a particle size of 2-4mm and 15kg of waste incineration fly ash are stirred and mixed to obtain a dry mixture; 30kg of river sand with a particle size of 0.2-0.5mm, 10kg of fly ash, 25kg of cement, and 8kg of tobacco carbon composite adsorption powder are stirred and mixed, 3kg of binder, 0.5kg of polycarboxylic acid high-efficiency water reducer and 10.5kg of water are added, wherein the binder is a mixture of polyvinyl alcohol and silica sol in a mass ratio of 1:1.5, stirred at 120r / min for 1.5min, then the dry mixture is added and stirred for 2min, after mixing evenly, transferred to a mold, vibrated for 30s, maintained at a pressure of 1.8MPa for 30s, and cured for 15 days at 25°C and a humidity of 95% after demolding to prepare gangue bricks, completing the process of preparing gangue bricks using tobacco and garbage ash.
[0050] Comparative Example 1: Based on Example 3, no tobacco carbon composite adsorption powder was added, and the other steps remained unchanged to prepare coal gangue bricks.
[0051] Comparative Example 2: Based on Example 3, the tobacco carbon composite adsorption powder was replaced with hydroxyapatite composite tobacco carbon powder of the same mass, and the other steps remained unchanged to prepare coal gangue bricks.
[0052] Comparative Example 3: Based on Example 3, the waste incineration fly ash is replaced with fly ash of the same mass, and the other steps remain unchanged to prepare coal gangue bricks.
[0053] Comparative Example 4: Based on Example 3, the waste incineration fly ash was replaced with calcium oxide powder of the same mass, and the other steps remained unchanged to prepare coal gangue bricks.
[0054] The contents of various oxides in the coal gangue in the embodiments and comparative examples are shown in Table 1:
[0055] Table 1
[0056] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> <![CDATA[SO3]]> <![CDATA[K20]]> CaO <![CDATA[TiO2]]> Percentage content (%) 40.546 29.285 10.529 14.313 1.038 0.792 1.525
[0057] Performance tests were performed on Examples 1 to 3 and Comparative Examples 1 to 4. The water permeability coefficient and splitting tensile strength of different gangue bricks were tested according to GB / T25993-2010. Leaching tests were performed on different gangue bricks according to HJ I300-2007. The leaching rates of chromium and lead in the corresponding gangue bricks were determined according to GB 7467-87. The results are shown in Table 2:
[0058] Table 2
[0059] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 <![CDATA[Coefficient of permeability (×10 -2 cm / s)]]> 2.83 2.65 2.51 2.45 2.49 2.56 2.42 Splitting tensile strength (MPa) 3.64 3.82 3.87 3.40 3.86 2.63 3.05 Chromium leaching rate (%) 0.004 0.003 0.003 0.127 0.082 0.004 0.003 Lead leaching rate (%) 0.006 0.005 0.006 0.181 0.115 0.006 0.005
[0060] As can be seen from Table 2, the gangue bricks in Examples 1 to 3 have higher splitting tensile strength, and the leaching rates of chromium and lead are lower. The leaching rates of chromium and lead in Comparative Example 1 increased because the tobacco carbon composite adsorption powder has a good adsorption and fixation effect on heavy metals, and combined with Comparative Example 2, it shows that the product containing dithiocarbamate functional groups plays a major role in fixing heavy metals; the splitting tensile strength in Comparative Example 3 is because the calcium oxide content in the waste incineration fly ash is higher, which helps the silicon oxide and aluminum oxide in the raw materials to generate hydrated calcium silicate and hydrated calcium aluminate, forming a high-strength network structure, thereby increasing the splitting tensile strength of the gangue brick; Comparative Example 4 shows that directly adding calcium oxide powder will make its content too high, resulting in excessive expansion of the gangue brick during the hydration process, which is not conducive to improving the splitting tensile strength of the gangue brick.
[0061] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0062] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A process for preparing coal gangue bricks using tobacco and garbage ash, characterized in that: The steps include: The gangue coarse aggregate, the gangue fine aggregate and the waste incineration fly ash are stirred and mixed to obtain a dry mixture; river sand, fly ash, cement and tobacco carbon composite adsorption powder are stirred and mixed, and then a binder, a water reducer and water are added, and the mixture is stirred at 100-120r / min for 1-1.5min, and then the dry mixture is added and stirred for 1.5-2min, and the mixture is transferred to a mold and vibrated for 20-30s, and a pressure of 1.6-1.8MPa is maintained for 25-30s, and the mold is demoulded, and the mixture is cured at 20-25°C and a humidity of 90-95% for 12-15 days to prepare a gangue brick, thereby completing the process of preparing a gangue brick using tobacco and garbage ash; The tobacco-carbon composite adsorption powder is prepared by the following steps: The silane coupling agent modified composite tobacco carbon powder and the mixed solvent are added to a reactor and stirred and mixed, and then triethylenetetramine is added, and amination is carried out at 70-80°C and 200-300r / min with stirring for 2.5-3h, and carbon disulfide and sodium hydroxide are added to the reactor at 25°C, and the reaction is stirred for 2-2.5h, and the filter cake is washed and vacuum dried to obtain tobacco carbon composite adsorption powder; the mixed solvent is prepared by mixing ethylene glycol and deionized water in a volume ratio of 1:
1.
2. A process for preparing coal gangue bricks using tobacco and garbage ash according to claim 1, characterized in that: The mass ratio of the gangue coarse aggregate, the gangue fine aggregate, the garbage incineration fly ash, the river sand, the fly ash, the cement, the tobacco carbon composite adsorption powder, the binder, the water reducing agent and the water is 60-70:30-40:10-15:20-30:5-10:15-25:5-8:2-3:0.4-0.5:7.5-10.
5.
3. The process for preparing coal gangue bricks using tobacco and garbage ash according to claim 1, characterized in that: The particle size of the gangue coarse aggregate is 5-10 mm, the particle size of the gangue fine aggregate is 2-4 mm, and the particle size of the river sand is 0.2-0.5 mm.
4. The process for preparing coal gangue bricks using tobacco and garbage ash according to claim 1, characterized in that: The binder is prepared by mixing polyvinyl alcohol and silica sol in a mass ratio of 1:1-1.
5.
5. The process for preparing coal gangue bricks using tobacco and garbage ash according to claim 1, characterized in that: The water reducer is a naphthalene-based water reducer or a polycarboxylic acid high-efficiency water reducer.
6. The process for preparing coal gangue bricks using tobacco and garbage ash according to claim 1, characterized in that: The dosage ratio of the silane coupling agent modified composite tobacco carbon powder, the mixed solvent, triethylenetetramine, carbon disulfide and sodium hydroxide is 1g:40-50mL:1-1.5g:0.66-0.995g:6g.
7. The process for preparing coal gangue bricks using tobacco and garbage ash according to claim 1, characterized in that: The silane coupling agent modified composite tobacco carbon powder is prepared by the following steps: Add hydroxyapatite composite tobacco carbon powder, anhydrous ethanol, deionized water and silane coupling agent KH-550 into a reaction kettle, adjust the pH value to 3 with acetic acid, stir at 200-300 r / min for 15-30 min, then ultrasonically disperse for 15-30 min, stir at 65-70° C. for 3-4 h, filter, wash the filter cake, and vacuum dry to obtain silane coupling agent modified composite tobacco carbon powder; The dosage ratio of the hydroxyapatite composite tobacco carbon powder, anhydrous ethanol, deionized water and silane coupling agent KH-550 is 10g:100mL:50mL:3g.
8. The process for preparing coal gangue bricks using tobacco and garbage ash according to claim 7, characterized in that: The hydroxyapatite composite tobacco carbon powder is prepared by the following steps: Add tobacco carbon powder, calcium chloride and deionized water into a reaction kettle, stir and mix, then add diammonium hydrogen phosphate, adjust the pH value to 10-10.5 with ammonia water, stir at 200-300 r / min for 2-2.5 hours, stand and age for 20-24 hours, filter by suction, wash the filter cake, and vacuum dry to obtain hydroxyapatite composite tobacco carbon powder; The usage ratio of the tobacco carbon powder, calcium chloride, deionized water and diammonium hydrogen phosphate is 2-2.5g:11g:180-200mL:7.9g.
9. A process for preparing coal gangue bricks using tobacco and garbage ash according to claim 8, characterized in that: The tobacco carbon powder is prepared by the following steps: The dry tobacco is cut into small pieces with a diameter of 3±0.5cm, then crushed with a pulverizer, passed through a 50-60 mesh sieve, and the tobacco powder is evenly mixed with coal gangue catalytic particles in a mass ratio of 5-6:1, transferred to a carbonization furnace, and heated to 300-320℃ at a rate of 3-5℃ / min under nitrogen protection, kept warm for 100-120min, cooled naturally, passed through a 60 mesh sieve, and the coal gangue catalytic particles are screened out to obtain tobacco carbon powder.
10. The process for preparing coal gangue bricks using tobacco and garbage ash according to claim 9, characterized in that: The coal gangue catalytic particles are prepared by the following steps: The coal gangue is crushed, sieved and transferred to a tubular furnace. Under nitrogen protection, the temperature is raised to 800-820°C at a rate of 5-10°C / min, kept warm for 50-60 minutes, and cooled naturally to obtain coal gangue catalytic particles with a particle size of 1-1.2 mm.
Citation Information
Patent Citations
Greening matrix of gangue crushing material and plant restoration technical method
CN102399111A